2013
DOI: 10.1118/1.4773885
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic model of cell survival for high-Z nanoparticle radiotherapy

Abstract: The presented stochastic framework can be used in interpretation of experimental cell survival or tumor control probability studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…59 In this approach, denoted as GNP-LQ to distinguish it from the extended LEM, 65 instead of the spatially averaged dose (or dose squared), a stochastic formulation is derived based on mixed Poisson distributions. The mathematical formulae of GNP-LQ differ from the average dose approach in the order of integration and may result in significantly different responses for the same level of external radiation and the same average concentration of GNPs, depending on the actual distribution of the nanoparticles among the population of cell.…”
Section: Dose Enhancement and Other Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…59 In this approach, denoted as GNP-LQ to distinguish it from the extended LEM, 65 instead of the spatially averaged dose (or dose squared), a stochastic formulation is derived based on mixed Poisson distributions. The mathematical formulae of GNP-LQ differ from the average dose approach in the order of integration and may result in significantly different responses for the same level of external radiation and the same average concentration of GNPs, depending on the actual distribution of the nanoparticles among the population of cell.…”
Section: Dose Enhancement and Other Metricsmentioning
confidence: 99%
“…In the case of GNPT, an equivalent uniform dose (EUD), D EUD , could be computed based on an accurate stochastic model and used for theoretical estimation of cell survival or RBE and compared with the experimental results. The GNP-LQ model accounts for the extreme dose heterogeneity that the cell experiences in the presence of GNPs by integrating the cell survival over the stochastic variable space 49,59 rather than taking an average dose:…”
Section: Dose Enhancement and Other Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a stochastic model of radiation dose enhancement has been described, representing the interactions of incident photons with aggregates of nanoparticles in cells. 20 In this work, we experimentally determined the optimal energy for dose enhancement by gold nanoparticles using a bovine aortic endothelial cell survival curve based on a viability assay as the measurement end point. A monoenergetic synchrotron beam in the range of 30-100 keV supplied by the BL20XU beam-line at the Spring-8 Biomedical Imaging…”
mentioning
confidence: 99%
“…Dose enhancement has been observed by inclusion of Au NPs with low energy X-ray beams (of the levels obtained from typical X-ray tubes) and to a much lower extent with higher energy beams (of the type generated by linear accelerators used in radiotherapy) [11][12][13]. Detailed descriptions of the outcomes of various studies have been recently reported by McMahon et al [16] as well as full theoretical studies of such methods for radiation dose enhancement [17]. Few studies have been documented in the literature describing alternatives to Au NPs [18].…”
Section: Time Course Of the Effect Of Nps On Pc3 Cell Viabilitymentioning
confidence: 99%